The Role of Multinational Pharmaceutical Companies in the Battle against COVID-19 - Baykara, Sıla Turac; Furfaro, Ricardo; Rajput, Muhammad Arif; Fernando, Jorge Tenorio (European Scientific Journal, ESJ, 2022)
This research aims to discuss how multinational pharmaceutical companies have responded to the challenges imposed by the COVID-19 pandemic, which would ideally be translated into supplying vaccines in a timely and efficient manner to fight against that emergency. The theoretical approach relies upon the concept of Corporate Social Responsibility (CSR), implying enterprises are supposed to achieve a balance of economic, social, and environmental deliverables while, at the same time, addressing the expectations of both shareholders and stakeholders. The method consists of scrutinizing secondary data—mainly figures of the vaccines provided by the different companies— and qualitative content analysis of the actions they state they have taken, which have been conveyed in press releases and annual reports. The findings show that major corporations have primarily considered the financial aspects of CSR, leaving out the social component they claim to address in their mission statements. Our critical position is that millions of lives could have been saved and relevant economic downturn avoided, particularly in low- and middle-income countries, had there been true practice and implementation of the CSR principles on the pharmaceutical company part.